PENENTUAN WAKTU PADA PERGERAKAN ELECTRIC SPRAY GUN UNTUK PROSES PENGECATAN POWDER COATING - Sjahrul, Yurika; Novita, Tita (UPPM Politeknik TEDC Bandung, 2025)
Powder coating is a painting process used to coat metal surfaces, providing a more durable and aesthetically pleasing finish compared to conventional painting. This method falls under the category of dry finishing, where the coating material is in the form of a fine powder consisting of a mixture of resin, color pigments, and other additives. The powder is electrostatically charged to adhere strongly to the cleaned metal surface. The coating process is carried out by spraying the powder using an electric spray gun, followed by a heating or oven curing process to melt and bond the powder permanently onto the metal surface. In an automated powder coating system, the movement of the electric spray gun and the metal object being coated is crucial to ensure uniform thickness and coating quality. For this purpose, two types of motors are used: a continuous rotation servo motor to rotate the object holder, and a DC motor to move the electric spray gun linearly. Both motors are controlled by an Arduino Uno microcontroller, which acts as the main control center, and an Omron CP1E PLC, which manages the overall industrial process control logic. The speed and movement time of the DC motor significantly affect the spray coverage distance. Based on testing, to reach a distance of 25 cm, the DC motor requires 3325 ms at a speed of 0.075 m/s. For a distance of 20 cm, the required time is 2670 ms, while for 15 cm, the motor runs for 2005 ms. These time calculations are essential to ensure that the metal surface area receives sufficient and even powder spray. With this system, the coating process can be performed automatically, efficiently, and consistently according to the programmed parameters.